2017
DOI: 10.12965/jer.1735028.514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy restriction and physical activity on brain function: the role of ketone body and brain-derived neurotrophic factor

Abstract: Brain development is a complex process, and stimuli during this development period may modulate the functional maturation of the brain. It has been shown that environmental stimuli, such as physical activity habits, have a beneficial effect on brain development. Endurance exercise and prolonged fasting state are known to improve brain function including cognition. The exact mechanisms of exercise improving brain function are still unknown. However, it can be considered that energy restriction and stressful cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our results suggest that the combination of multiple types of exercise, high effort, high intensity, and high training volume in a relatively short time (9 min) can be a decisive factor in the dynamics of post-exercise changes in BDNF. Here, we confirmed results already found by other research groups, whose purpose was to investigate the effects of more common types of exercises on alterations of this neurotrophin ( Seifert et al, 2010 ; Szuhany et al, 2015 ; Park and Kwak, 2017 ; Liu and Nusslock, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest that the combination of multiple types of exercise, high effort, high intensity, and high training volume in a relatively short time (9 min) can be a decisive factor in the dynamics of post-exercise changes in BDNF. Here, we confirmed results already found by other research groups, whose purpose was to investigate the effects of more common types of exercises on alterations of this neurotrophin ( Seifert et al, 2010 ; Szuhany et al, 2015 ; Park and Kwak, 2017 ; Liu and Nusslock, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is known that ageing increases DNA breaks and activates DNA-dependent protein kinase (DNA-PK) in skeletal muscle, suppressing mitochondrial function and energy metabolism [122]; PPAR-alpha activation counteracts this process, possibly resulting in a delay of metabolic decline with age [123]. Interestingly, this decline can be prevented with lifestyle modifications such as caloric restriction and/or physical activity [122].…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor has neurobiological and metabolic effects, regulating the survival (Hofer and Barde, 1988), growth (Kalcheim and Gendreau, 1988) and maintenance of neurons (Griesbeck et al, 1995). Its association with physical activity is already known (Almeida et al, 2016; Church et al, 2016); in fact, its expression not only increases after exercise (Park and Kwak, 2017) but also depends on the intensity of exercise (Jeon and Ha, 2017). Previous studies demonstrated that its mRNA and protein expression levels increase in human skeletal muscle after exercise without any release into the circulation (Matthews et al, 2009).…”
Section: Myokines and The Contracting Musclementioning
confidence: 98%